Analisis Pelaksanaan Ekstensifikasi Pajak Sektor Usaha Mikro Kecil Dan Menengah Dalam Rangka Meningkatkan Penerimaan Pajak Tahun 2020 (Studi Kasus Di KPP Pratama Bekasi Utara) - Ines Citra Risqiqa; Rahadi Pratomo Singgih (Jurnal Ilmu Administrasi Publik, 2021)
This research was conducted to find out how the Tax Extensification of the Micro,Small and Medium Enterprises Sector to Increase Tax Revenue in 2020 at KPP Pratama, North Bekasi. The results of this study indicate that the number of taxpayers at KPP Pratama Bekasi Utara in 2019 to 2020 always increases, both for personal taxpayers and corporate taxpayers, but in terms of tax revenue, it always experiences significant changes every year. In this study, the author uses the theory put forward by Seomitro in Lovena Dewi (2016) in which there are 3 dimensions, namely: Expansion, Adjustment, and Expansion of Objects. The approach used in this research is a qualitative approach with a descriptive method. Collecting data in this study is by observation, documentation, and interviews. The results of this study indicate that the implementation of tax extensification in the MSME sector in terms of the expansion of  taxpayers is carried out based on general extensification rules such as through the provision of appeal letters, sweeping to the KPP work area or to the taxpayer's location, through a one-way information system/sms flashting, and pamphlets. Meanwhile, tax extensification in terms of tariff improvement and tax object expansion is the authority of the government as a policy maker.